Predictors of poor mid-term health related quality of life after primary isolated coronary artery bypass grafting surgery. Issue 12 (14th November 2005) - Al-Ruzzeh, S; Athanasiou, T; Mangoush, O; Wray, J; Modine, T; George, S; Amrani, M
Abstract : Objective: To assess the determinants of poor mid-term health related quality of life (HRQoL) at one year after primary isolated coronary artery bypass grafting (CABG). Methods: 463 patients who underwent primary isolated CABG for multivessel disease and came for their annual follow up at the outpatient clinic during one year at Harefield Hospital, Middlesex, were approached to participate in the present study. Prospective clinical data were collected as part of the clinical care of the patients and were retrospectively analysed when the patients consented to participate in the study at their outpatient visit. After their consent they were given three HRQoL assessment questionnaires. Scores, together with clinical data, were analysed by both univariate and multivariate analyses with regard to poor HRQoL outcome. Results: 437 (94.4%) patients consented to participate in the study and filled in the HRQoL questionnaires. Ten variables were identified in the univariate analysis as potential predictors of poor scores of the physical element of HRQoL; however, only three variables—gastrointestinal problems, congestive heart failure, and type D personality trait—predicted poor physical scores independently. Eleven variables were identified in the univariate analysis as potential predictors of poor scores of the mental element of HRQoL; however, only three variables—peripheral vascular disease, infective complications, and type D personality trait—predicted poor physical scores independently. Conclusion: Preoperative gastrointestinal problems, preoperative congestive heart failure, and type D personality trait were independent predictors of the poor physical component of HRQoL. Peripheral vascular disease, infective complications, and type D personality trait were independent predictors of the poor mental component of HRQoL. Interestingly, patients with type D personality were more than twice as likely to have poor physical HRQoL and more than five times as likely to have poor mental HRQoL.